SYNTACTICAL STRUCTURE OF BINARY TAUTOLOGISMS - Normurodova Soxiba (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
It is well known that teaching depends on what is being taught. Consideration of these factors should ensure the success of the lesson. The effectiveness of the lesson is largely determined by the thoroughness of preparation for it.